2020
DOI: 10.3390/plants9080957
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Potential Current and Future Distribution of the Endangered Endemic Vascular Plant Primula boveana Decne. ex Duby in Egypt

Abstract: Knowledge about population attributes, current geographic distribution, and changes over predicted climate change for many threatened endemic vascular plants is particularly limited in arid mountain environments. Primula boveana is one of the rarest and threatened plants worldwide, surviving exclusively in Saint Catherine Protectorate in the Sinaic biogeographic subsector of Egypt. This study aimed to define the current state of P. boveana populations, predict its current potential distribution, and use the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 86 publications
(149 reference statements)
8
20
0
Order By: Relevance
“…MAXENT is reliable in predicting the potential geographic distributions of species [19][20][21]23]. Ardestani reported that [22] the species with a wide distribution range tend to have low AUC values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MAXENT is reliable in predicting the potential geographic distributions of species [19][20][21]23]. Ardestani reported that [22] the species with a wide distribution range tend to have low AUC values.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that soil factors can accurately limit the distribution range of species on the basis of climate factors, and the accuracy of climate and soil models for C. acuminata is high. Abdelaal [23] suggested that combining climate variables with soil variables can predict the distribution of species accurately. In the present study, climate, topographic, and soil variables were combined to explore the potential habitat distribution shift in current and future periods of four alpine Rhododendron species under rapid climate change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research of different regions has reported variables found to have an important effect on various species. For example: Evangelista, Young & Burnett, 2013 Studied teff by using three climate projection model that the value of predictable were 0.79 (Bio16, Bio12, Bio19, Bio15) and others studied different species in different geographical area including, (Elham et al, 2015) (Bio2, Bio3, Bio7, Bio8, Bio13, Bio14, Bio15, Bio18), ( Ardestani et al, 2015 ) (Bio8, Bio19, Bio2, Bio13, Bio7), Sen et al, 2016 (Bio4 and Bio19), Rong et al, 2019 (Bio1, Bio8 and elevation), ( Abdelaal et al, 2020 ) (elevation, precipitation, temperature and soil), and Yang et al, 2020 (Temp Seasonality, Precipitation, Vegetation Type, Soil Type). Our results indicate that temperature of coldest quarter had a predictability value of 0.83 for teff, which is stronger than that of any other existing model.…”
Section: Discussionmentioning
confidence: 99%
“…climatic, topographic, landscape) with the occurrence of species in one particular area (Guisan and Zimmermann 2000;Hirzel et al 2002) determining the PHS of each species. During the last years, studies in plant species distribution were significantly increased (Bradley et al 2012), mostly related to woody species (Silva et al 2017), and invasive (Chai et al 2016;Wan and Wang 2018) or endangered plant species (Abdelaal et al 2020). Nevertheless, few studies combined multiple PHS to create a unique potential biodiversity map (PBM) that synthetizes the information for multiple species at the landscape level (e.g.…”
Section: Introductionmentioning
confidence: 99%